A review of tax avoidance in China - Tanya Y. H. Tang (China Journal of Accounting Research, 2020)
This paper synthesizes the major empirical findings of the burgeoning tax avoidance research in China from the accounting, finance, and economics literature over the last 13years. It surveys the evidence in four main areas: (1) the mechanisms through which Chinese firms avoid income taxes; (2) the effects of government ownership and agency problem on tax avoidance; (3) tax avoidance and political connections; and (4) the roles of book-tax conformity, tax enforcement, and corporate governance. It also discusses the appropriateness of tax avoidance measures in the Chinese setting. Finally, it proposes important directions for future research.
Keywords: 650; Tax avoidance; Government ownership; Agency problems; Corporate political activity; Book-tax conformity; China